PENGEMBANGAN KOMODITAS PORANG DI KABUPATEN ALOR - Gerson Hans Maure; Ferdinan Demang; Frengki I. Malese; Onesimus Mowata (JURNAL AGRIMANSION, 2025)
Porang (Amorphophallus muelleri) is a tuber plant in Indonesia that has existed since ancient times. Porang plants in Alor grow naturally and wild without proper cultivation practices. The study was conducted to analyze the strengths, weaknesses, opportunities, and challenges of porang cultivation and to formulate a strategy for sustainable porang development. The study was conducted in the districts of East Alor, Northeast Alor, Southwest Alor, and Lembur from June to September 2025. The method used in this study was descriptive qualitative. The data in this study were primary and secondary data. Secondary data were obtained through interviews with 72 respondents who were determined by purposive sampling. The interviews used a structured questionnaire that referred to internal and external factors of the porang commodity with a Likert scale (scale 1-4), and secondary data from journals, publications, and various related literature. The data were then analyzed using a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to obtain information regarding strengths, weaknesses, opportunities, and threats. The SWOT analysis results indicate that porang in Alor Regency has the potential for development, requiring aggressive strategies to ensure successful growth and development of porang farming. Porang development in Alor follows a Strength-Opportunity (SO) strategy, leveraging strengths to seize opportunities. This strategy aims to increase porang productivity by maximizing land and climate suitability, increasing farmer capacity through government support, building export and management networks, utilizing local seeds, and expanding planting areas by maximizing local labor resources